Discoveries in Pancreatic Physiology and Disease Biology Using Single-Cell RNA Sequencing - Fu, Haotian; Sun, Hongwei; Kong, Hongru; Lou, Bin; Chen, Hao; Zhou, Yilin; Huang, Chaohao; Qin, Lei; Shan, Yunfeng; Dai, Shengjie (Frontiers in Cell and Developmental Biology, 2022)
Transcriptome analysis is used to study gene expression in human tissues. It can promote the discovery of new therapeutic targets for related diseases by characterizing the endocrine function of pancreatic physiology and pathology, as well as the gene expression of pancreatic tumors. Compared to whole-tissue RNA sequencing, single-cell RNA sequencing (scRNA-seq) can detect transcriptional activity within a single cell. The scRNA-seq had an invaluable contribution to discovering previously unknown cell subtypes in normal and diseased pancreases, studying the functional role of rare islet cells, and studying various types of cells in diabetes as well as cancer. Here, we review the recent in vitro and in vivo advances in understanding the pancreatic physiology and pathology associated with single-cell sequencing technology, which may provide new insights into treatment strategy optimization for diabetes and pancreatic cancer.